PENGARUH MODEL KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING TERHADAP KETERAMPILAN PROSES SAINS SISWAKELAS VII MATERI CIRI-CIRI MAKHLUK HIDUP DI MTs NEGERI 2 PALEMBANG - Fajri Ismail; Yustina Hapida; Destianah Destianah (Bioilmi: Jurnal Pendidikan, 2017)
Education plays an important role in the intellectual life of the nation from time to time so, thereis a needs to do an effort to improve the quality of education. Improving the quality of educationcan be seen from the success of formal education in the form of student learning outcomes toimprove the quality of education and the development of teaching systems. Currently manykinds of learning models aims to improve the quality of learning to be better one of them is acooperative model. In using the learning model sometimes teachers have to adjust to thecondition and atmosphere of the classroom. As an alternative that can be applied is a modelcooperative type student facilitator and explaining. This research aims to know the influence ofcooperative model of student facilitator and explaining type to the science process skill of VIIstudents of MTs Negeri 2 Palembang Which was held in August 2016.. This research designuses posttest-Only control design with quasi-experiment method. The study population is 192students with the sample of research which amounted to 64 students. The average result of thisresearch is 83,43 and the control class is 79,37. Normality test results of 0.142 <0.05 andhomogeneous test results of 0.268 <0.05 which means the data is normal and homogeneous. The result of t-test calculation is 4.686 > 1.66980 or P-value (sig) is 0.000, because P-value <á, Ha is accepted and H is rejected. Thus, it can be concluded that cooperative model ofstudent facilitator and explaining type have an effect on science process skill of VII students of MTs Negeri 2 Palembang